Sperm epigenetics and influence of environmental factors - Ida Donkin; Romain Barrès (Elsevier, 2018)
Background: Developmental programming of the embryo is controlled by genetic information but also dictated by epigenetic information contained in spermatozoa. Lifestyle and environmental factors not only influence health in one individual but can also affect the phenotype of the following generations. This is mediated via epigenetic inheritance i.e., gametic transmission of environmentally-driven epigenetic information to the offspring. Evidence is accumulating that preconceptional exposure to certain lifestyle and environmental factors, such as diet, physical activity, and smoking, affects the phenotype of the next generation through remodeling of the epigenetic blueprint of spermatozoa. Scope of Review: This review will summarize current knowledge about the different epigenetic signals in sperm that are responsive to environmental and lifestyle factors and are capable of affecting embryonic development and the phenotype of the offspring later in life. Major conclusions: Like somatic cells, the epigenome of spermatozoa has proven to be dynamically reactive to a wide variety of environmental and lifestyle stressors. The functional consequence on embryogenesis and phenotype of the next generation remains largely unknown. However, strong evidence of environmentally-driven sperm-borne epigenetic factors, which are capable of altering the phenotype of the next generation, is emerging on a large scale. Keywords: Sperm, Spermatozoa, Epigenetic, Epigenetic inheritance, Small RNA, DNA methylation, Histone